Analysis of the Impact of Recruitment and Selection as a Strategic Human Resource Management Tool on Organisational Performance in Zambia - Mwambela, Able (Journal of Management Studies and Development, 2024)
The effective management of human resources is paramount for achieving organizational performance at various operational levels.  The oversight of human resources can significantly disadvantage an organization.  This research aims to scrutinize the influence of recruitment and selection as a Strategic Human Resource Management (SHRM) component on organizational performance.  The study encompassed 169 managers from profit-making organizations in Zambia and employed a quantitative approach to gather data through a structured questionnaire.  The questionnaire was structured into three parts: the first part gathered demographic data, the second part collected information about SHRM practices, and the third part obtained data relating to organizational performance.  A study was conducted on 169 managers from various organizations using a stratified random sampling method.  The findings confirmed the reliability of the data collection tool.  Notably, the study revealed that managers placed the highest importance on incentives and rewards as factors influencing excellence, followed by recruitment and selection, formal performance appraisal, and with the least emphasis on career development.  According to the study, there is a significant correlation between Strategic Human Resource Management (SHRM) components and organizational performance.  This includes the revenue growth rate, return on equity, return on assets, and overall profitability (p < 0.01).  Therefore, the study suggests that organizations should align their SHRM strategy with other activities that lead to improved performance, especially in the recruitment process, as it directly impacts the organization's products.  The study concludes that Strategic HRM practices are crucial in driving organizational performance and should be integrated with overall business strategies and operations to maximize benefits.